A Combined Experimental–Computational Investigation to Uncover the Puzzling (Chiro‐)optical Response of Pyridocyclophanes: One‐ and Two‐Photon Spectra. Issue 34 (14th July 2015) - Padula, Daniele; Lahoz, Inmaculada R.; Díaz, Carlos; Hernández, Florencio E.; Di Bari, Lorenzo; Rizzo, Antonio; Santoro, Fabrizio; Cid, M. Magdalena
Abstract A combined experimental–computational analysis of the one‐ and two‐photon absorption (OPA, TPA) and the electronic circular dichroism (ECD) of complex chiral shape‐persistent (2, 6)‐pyrido[142]allenoacetylenic cyclophane, (P, P, P, P)‐MC[142] enantiomers, sheds light on the origin of their peculiar spectral signatures. The study on MC[142], which is represented in solution by three possible conformers, indicates that two of them (chair and twist) are the prevalent conformers at room temperature; the population ratio depending on the solvent. The complex shape of the red‐edge of the UV and ECD spectra is qualitatively reproduced by using vibronic calculations and assigned to progressions on the ethynyl stretchings observable only in the chair and twist conformers. The picture arising from the analysis of the linear spectra is confirmed by two‐photon spectroscopies, showing that they constitute valuable tools for the exploration of high‐energy electronic transitions in pyridoallenoacetylenic cyclophanes. Discrepancies among computed and experimental spectra point out that an accurate description of such complex systems with a large delocalized π framework and a dense manifold of electronic excited state remains a challenge for theoretical models.